Antioxidant Studies and Characterization of Cassia tora (Sickle Senna) Seeds Oil - Hassan Galadima, Muhammed; Mukhtar Mohammed, Abdussamad; Umar, Sani (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Cassia tora seeds were utilized in ancient healthcare systems to cure numerous symptoms and disorders. Recently, there has been widespread information about the potency of the seed to cure even eye ailments like glaucoma. However, there is no systematic scientific backing or research explaining the detailed character of the seeds and their oil; as such investigation into its properties is required now more than ever. N-hexane, ethyl acetate, and distilled water were used to extract the oil from fresh Cassia tora seeds. The extracted oil's antioxidant potential was evaluated, and scavenging activity investigations were conducted. The results revealed an interesting antioxidant activity of the oil compared to standard antioxidants, signifying its potential in various applications and products. The FTIR spectroscopy confirmed the presence of hydroxyl, esters, aliphatic hydrocarbon, carbonyls, aldehyde, and unsaturated bonds which are characteristic of fatty acids and triglycerides. The saponification value of 187.71 mg KOH/g, an iodine value of 7.64 mg/g, and an acid value of 1.19 mg/g were obtained. The numerous results obtained in this study reinforced the potential of Cassia tora oil in various applications, including its potential to be employed as an antioxidant or part of formulations of various effective antioxidants.